PARTICIPATORY PLANNING WITH GENDER PERSPECTIVE FOR ECONOMIC EMPOWERMENT IN KLAMBIR 5 COMMUNITY - Annisa Ilmi Faried; Annisa Sanny; Yunita Fitriana (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
Community development in rural areas requires an inclusive approach that recognizes the vital role of women in economic transformation. This research explores the implementation of gender-based participatory planning as a strategy for sustainable local economic empowerment in Klambir 5 Village, Deli Serdang Regency. Through a qualitative descriptive approach involving 45 community members, this study reveals how women's active involvement in planning processes creates more responsive and sustainable development outcomes. The findings demonstrate that participatory mechanisms incorporating gender perspectives significantly enhance women's economic capacity, strengthen community social capital, and foster locally-driven sustainable development. This study contributes to the discourse on inclusive development by presenting an empirical model where gender-sensitive participatory planning becomes a catalyst for equitable economic growth. The research concludes that recognizing women as development agents, not merely beneficiaries, fundamentally transforms the effectiveness of rural economic empowerment initiatives.